Mecurate stud finder wall scanner sensor [library of things] (Merurate Instrument, 2022)
The stud finder is equipped with 5 scanning modes, each tailored to specific applications. Among these modes are the 3/4" and 1-1/2" scanning mode, designed to identify the center and edge of woods, beams, joists, metals, and deeply embedded objects. The metal scanning mode is engineered to detect both ferrous and non-ferrous metals. Additionally, an audible alert buzzer mode is provided to signal the detection of a stud or other object. --